Organised crime and the role of law and law enforcement agencies in Ghana - Yin, Elijah Tukwariba (Economic and societal impact of organized crime, 2024)
This chapter brings together the various components of organised crime in Ghana and analyses the role of law and law enforcement agencies. It is argued that organised crime in Ghana undermines the emerging fragile democratic institutions in the country. Rooted in transparency, press freedom, rule of law, and free and fair elections, some elected and/or appointed officials who have taken oaths of office to defend the Constitution without fear or favour have largely been compromised to do the bidding of criminal syndicates at the expense of citizens. Despite the improvement in legislation and the coordinated efforts of mandated state agencies, the influence of affluent organised criminal syndicates on some law enforcement agencies has weakened state-agency collaboration. The undermining role of politicians presents a paradox of power subversion that aids and abets organised criminal activities. Sophisticated technology, political preparedness, and individual alertness are crucial in dealing with organised crime in Ghana.